Corynebacterium megadyptis sp. nov. with two subspecies, Corynebacterium megadyptis subsp. megadyptis subsp. nov. and Corynebacterium megadyptis subsp. dunedinense subsp. nov. isolated from yellow-eyed penguins. - Nouioui I; Saunderson SC; Midwinter AC; Young MJ; McInnes KM; Watts J; Sangal V (Microbiology Society, 2023)
Novel Corynebacterium strains, 3BT and 7BT, were isolated from the oral cavities of young chicks of yellow-eyed penguins (hoiho), Megadyptes antipodes. A polyphasic taxonomic characterization of these strains revealed chemotaxonomic, biochemical and morphological features that are consistent with those of the genus Corynebacterium. The 16S rRNA gene sequence similarity values between the strains and their closest phylogenetic neighbour, Corynebacterium ciconiae CCUG 47525T were 99.07 %, values that are in line with their phylogenomic positions within the evolutionary radiation of the genus Corynebacterium. Digital DNA-DNA hybridization values and average nucleotide identities between the genome sequences of the two strains and related Corynebacterium species were well below the defined threshold values (70 and 95-96 %, respectively) for prokaryotic species delineation. The genome size of these strains varied between 2.45-2.46 Mb with G+C content 62.7-62.9 mol%. Strains 3BT and 7BT were Gram-stain positive bacilli that were able to grow in presence of 0-10 % (w/v) NaCl and at temperature ranging between 20-37 °C. The major fatty acids (>15 %) were C16 : 0 and C18 : 1  ω9c, and the mycolic acid profile included 32-36 carbon atoms. We propose that these strains represent a novel species, Corynebacterium megadyptis sp. nov. with 3BT (=DSM 111184T=NZRM 4755T) as the type strain. Phylogenomically, strains 3BT and 7BT belong to two lineages with subtle differences in MALDI-TOF spectra, chemotaxonomic profiles and phenotypic properties. The fatty acid profile of strain 3BT contains C18 : 0 as a predominant type (>15 %), which is a minor component in strain 7BT. Strain 7BT can oxidize N-acetyl-d-glucosamine, l-serine, α-hydroxy-butyric acid, l-malic acid, l-glutamic acid, bromo-succinic acid and l-lactic acid, characteristics not observed in strain 3BT. Therefore, we propose that these strains represent two subspecies, namely Corynebacterium megadyptis subsp. megadyptis subsp. nov. (type strain, 3BT=DSM 111184T=NZRM 4755T) and Corynebacterium megadyptis subsp. dunedinense subsp. nov. (type strain, 7BT=DSM 111183T=NZRM 4756T).
Keywords: Corynebacterium megadyptis; Megadyptes antipodes; diphtheritic stomatitis; novel species; yellow-eyed penguin; Animals; Fatty Acids; Spheniscidae; Phylogeny; RNA, Ribosomal, 16S; Base Composition; DNA, Bacterial; Bacterial Typing Techniques; Sequence Analysis, DNA; Corynebacterium; Nucleic Acid Hybridization